Network Data Envelopment Analysis Foundations and Extensions - Kao, Chiang (Cham : Springer International Publishing : Imprint: Springer, 2023)
This second edition systematically presents the underlying theory, model development, and applications of network Data Envelopment Analysis (DEA). It discusses the models used to measure the efficiency of systems in specific network structures and introduces readers to the latest applications. It demonstrates how the "network DEA" approach helps identify and manage the specific components that cause inefficiencies in the overall system. The existing models for measuring the efficiency of systems in specific network structures are also discussed, and the relationships between system efficiency and component efficiency are explored. Moreover, the book provides an advanced exposition on performance evaluation of systems with network structures. It explores the networked nature of most production and operation systems, and explains why network analyses are necessary. Accordingly, the book will inspire new research and applications based on the state of the art. In this new edition, the latest research advances and discoveries are discussed. Two new chapters on Linkage Efficiency and External and Internal Evaluations have been added. This book is mainly aimed at researchers and graduate students who are interested in performance evaluation, DEA, and multi-criteria decision analysis. Practitioners who want to measure the performance of production, operation, or any type of decision-making units will also find it useful.
Introduction -- Output-Input Ratio Efficiency Measures -- Distance Function Efficiency Measures- Slacks-Based Efficiency Measures -- Efficiency Measurement in Special Production Stages -- Special Types of Input and Output Factors -- Special Types of Data -- Changes of Efficiency over Time -- Basic Ideas in Efficiency Measurement for Network Systems Basic Two-stage Systems -- General Two-stage Systems -- Multi-Stage Systems -- Parallel Systems -- Mixed Systems -- Dynamic Systems -- Linkage Efficiency -- External and Internal Evaluations -- Epilogue -- Index.
Keywords: Production management; Operations research; Management science; Operations Management; Operations Research and Decision Theory; Operations Research, Management Science .